Unveiling the Structural Properties, Optical Behavior, and Thermoelectric Performance of 2D CsSn 2 Br 5 Halide Obtained by Mechanochemistry - Lopez, Carlos Alberto (2024)
Metal halide perovskites with a two-dimensional structure are utilized in photovoltaics and optoelectronics. High-crystallinity CsSn2Br5 specimens have been synthesized via ball milling. Differential scanning calorimetry curves show melting at 553 K (endothermic) and recrystallization at 516 K (exothermic). Structural analysis using synchrotron X-ray diffraction data, collected from 100 to 373 K, allows for the determination of Debye model parameters. This analysis provides insights into the relative Cs–Br and Sn–Br chemical bonds within the tetragonal structure (space group: I4/mcm), which remains stable throughout the temperature range studied. Combined with neutron data, X–N techniques permit the identification of the Sn2+ lone electron pair (5s2) in the two-dimensional framework, occupying empty space opposite to the four Sn–Br bonds of the pyramidal [SnBr4] coordination polyhedra. Additionally, diffuse reflectance UV–vis spectroscopy unveils an indirect optical gap of approximately ∼3.3 eV, aligning with the calculated value from the B3LYP-DFT method (∼3.2 eV). The material exhibits a positive Seebeck coefficient as high as 6.5 × 104 μV K–1 at 350 K, which evolves down to negative values of −3.0 × 103 μV K–1 at 550 K, surpassing values reported for other halide perovskites. Notably, the thermal conductivity remains exceptionally low, between 0.32 and 0.25 W m–1 K–1.